AGRICULTURE AND MONITORING AGRICULTURE FIELD USING IOT - D., Pooja; J., Mohana (International Journal of Psychosocial Rehabilitation, 2020)
IoT looks like the future of connectivity & IT. IoT is now used in all fields, such as smart homes, intelligent cities, etc. IoT traffic control The IoT deployment area is wide and can be deployed in any country. Suggested work deals with IoT implementation in agriculture. IoT helps to improve crop production by better management of resources, cost-effective cultivation, better quality and quantity, monitoring of crops and fields, etc. In the proposed model, the IoT sensors used includes the air temperature sensor, the ph sensor of the earth, the moisture sensor, the water volume sensor, etc. The population is increasing and the land is decreasing on agricultural land due to different factors, such as industrialization, consumer markets and residential areas, and we need to increase production to feed these billions, and this can be done in agriculture through IoT. We need technological progress to get rid of these barriers and make agriculture more competitive, smart and comfortable for farmers.